LABIRYNTY MYSZKINA (PODRÓŻ SZESTOWOWSKA) - Kruszelnicki, Michał (Przegląd Rusycystyczny, 2017)
The aim of the paper is to present prince Myshkin’s highly complex, almost labyrinthine personality. Reading addresses and undermines all the homogenizing interpretations (e.g. Lev Shestov’s notoriously malevolent reading of Myshkin) that aim at discovering “one” truth about this character, be it positive or negative, and thus fail to acknowledge its contradictory elements. I also intend to show that the prince can be seen as much more of a “Shestovian,” tragic and divided figure as one could initially think. Shestov’s philosophical thought inspires the investigations, first as a starting point for the analysis of Myshkin criticisms in scholarly literature, then as a polemical reference, and finally as a basis for formulating a lead thesis. I am led to conclude that building Myshkin’s character, being as it is, largely inconsistent, insecure, and errant in his moral evaluations of other people, Dostoevsky opposed any attempts at exhausting, finalizing the identity of the other human being in the abstract net of rational interpretations. At the same time Dostoevsky most powerfully brought to light that which is most fragile, intimate and therefore prone to misunderstanding or a hasty critique — the tragedy of an individual life.